Peran Strategi Digital Marketing dan Interaksi Tatap Muka terhadap Keputusan Pembelian Konsumen Perusahaan Start-Up di Jawa Barat - Purnamasari, Pupung; Suriyanti; Gunawan , Ahmad; Berliana Putri , Fenina (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
This study evaluates the influence of digital marketing strategies and face-to-face interaction on consumer purchase decisions in start-up companies in West Java, with consumer preferences as a moderating variable. Employing a mixed-method approach, the research uses Structural Equation Modeling (SEM) for quantitative data analysis and thematic interviews for qualitative insights. The findings reveal that both strategies have a positive and significant impact on purchase decisions. Face-to-face interaction proves to have a stronger influence in building trust and increasing purchase intention, while digital marketing strategies are effective in generating initial awareness. Consumer preferences moderate the impact of face-to-face interaction, indicating that personal experiences are favored by the majority of consumers. These findings support the theories of Customer Engagement and Trust-Building, and highlight the importance of an omnichannel approach that integrates both digital and in-person strategies to create a holistic consumer experience. The study recommends that start-ups adopt integrated marketing strategies to enhance customer loyalty and campaign effectiveness. Future research may explore the role of advanced technologies in strengthening this integration and their impact on consumer behavior. Keywords: Digital marketing, face-to-face interaction, consumer purchase decision, consumer preferences, start-up.